Image Super-Resolution Using Sparse Representation And Novelty Noise Removal Super-Resolution - Ahmed, Saab Hazim; Kurnaz, Sefer; Mohammed, Alaa Hamid (2020 4th International Symposium on Multidisciplinary Studies and Innovative Technologies (ISMSIT), 2020)
The reconstruction of a composite image with a super-resolution will produce a high-resolution image from a low-resolution picture. Since the super-resolution problem is not well answered, a narrow method of optimizing numeric algorithm is implemented to remove image noise. The total variation of the image is minimized subject to noise statistical constraints. The restrictions are imposed on the use of Lagrange multipliers. The solution is derived from the gradient projection method. It is the solution of a partial differential equation based on time based on several constraints described. As t--\sim0o, the solution converges into a continuous image. It is a fast, relatively easy numerical algorithm. The measurements are typically state of the art with very noisy videos. The process is non-invasive, which gives straight boundaries to the picture. A first step to the transfer can be translated. level range of the normal image at a pace equivalent to the level curvature separate from the magnitude of the feature gradient, and a second stage for the return to the boundary point of the picture.